Identification and comparison on chemical compositions of citrus aurantifolia oh. Of hydro distilation and hexane extracts / Norain Sabli - Sabli, Norain (Faculty of Applied Sciences, 2009)
In this study, essential oils of key lime (Citrus aurantifolia) from peel and fruit were obtained by two different methods, hydro distillation essembly clavenger-type apparatus and hexane extracts. The GCMS analysis identified different substances presence in both methods being limonene, p-pinene, a-bisabolol, and a-terpineol which the most significant compounds. These chemical compounds can be represented by three main classes; terpenes, sesquiterpenes, and oxygenated compounds. Extract of essential lime peel oil by hydro distillation produced 10.43% oil yield and consists of 62.61% terpene hydrocarbon groups, 17.94% sesquiterpene, and about 19.45% of oxygenated compound groups. However, hexane extracts produced half amount of hydro distillate yield which is 5.44% and 1.80% for peel arid fruit respectively. The main chemical components of hexane extracts being 35.9% of terpene hydrocarbon groups, 29.9% of sesquiterpene compound groups, and 23.51% oxygenated compounds.